Pengaturan Pendaftaran Tanah Timbul (Aanslibing) dalam Rangka Mewujudkan Kepastian Hukum di Indonesia - Marrio Ekasaputra; Iyah Faniyah; Otong Rosadi (UNES Law Review, 2023)
Land is the main source of people's prosperity and well-being. In an effort to control and own limited areas of land, sometimes people try to control and own emerging land. There is no definite data on the extent of state land originating from emerging land, so the process of controlling emerging land is outside the state's control. The BAL does not specifically regulate the issue of emerging land, but in a general formulation, that emerging land is under state control. Judicial regulation regarding emerging land, starting with the Minister of State for Agrarian Affairs Decree Number 410-1293 of 1996 concerning Controlling the Status of Rising Land and Reclamation Land and ATR/KBPN Ministerial Regulation No. 17 of 2016 concerning Land Management in Coastal Areas and Small Islands and PP no. 16 of 2004 concerning Land Use Management. Until now there has not been found a law that strictly regulates the existence of land arising. This research is a legal research with descriptive analytical research specifications. The approach used in this study is a normative juridical approach. The data used are secondary data obtained through library research and document studies. The data was then analyzed qualitatively and presented in a qualitative descriptive form.